STRATEGI PENGEMBANGAN USAHA PRODUKSI OLAHAN IKAN SIDAT (Anguilla bicolor) PT. JAWA SUISAN INDAH, SUKABUMI - Rismah Rismah; Muhamad Karim; Yodfiatfinda Yodfiatfinda (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
PT. Java Suisan Indah is an agribusiness company engaged in eel farming where the products are purposed to export market.  The company is still facing difficulties in fulfilling the quality stock of eel raw materials, due to high mortality in the cultivation stage and availability of eel seeds as well. The goals  of this study are (i) to identifies internal and external factors that influence the business development system of PT. JSI and, (ii) to formulating the alternative strategies in order to prioritize business development that can be applied at PT. JSI. The sampling method  uses a purposive sampling technique where respondents act as expert adjustments. The results of this study are concluded; (i) PT JSI must maintain prices and improve the quality of eel processed products by prioritizing distinctive flavors accompanied by diverse product variants to increase international consumer loyalty to PT JSI's products. This strategy based on QSPM analysis obtained a STAS value of 6.862 ; (ii) intensifying and promoting processed eel products through social media for the domestic market to expand sales and be widely known to the public. This strategy based on QSPM analysis obtained a STAS value of 6.514. And (iii) applied a plasma core-core partnership model between PT JSI as the core and eel farmers as plasma. This partnership process is carried out to meet and increase the need for a stock of raw materials to produce eel forceps. This strategy based on QSPM analysis obtained a STAS value of 6.426.